Plasma Factor XIII and Platelet Factor XIII in Hyperlipaemia - Cucuianu, Mircea P.; Miloszewski, K; Porutiu, D; Losowsky, M. S (Thrombosis and Haemostasis, 1976)
Plasma factor XIII activity measured by a quantitative assay was found to be significantly higher in hypertriglyceridaemic patients (type IV and combined hyperlipoproteinaemia), as compared to normolipaemic controls. No such elevation in plasma factor XIII activity was found in patients with type IIa hyperlipaemia. Plasma pseudocholinesterase was found to parallel the elevated factor XIII activity in hypertriglyceridaemic subjects.In contrast, platelet factor XIII activity was not raised in hyperlipaemic subjects, and plasma factor XIII was found to be normal in a normolipaemic subject with throm-bocythaemia.It was concluded that there is no significant contribution from platelets to plasma factor XIII activity, and that the observed increase in plasma factor XII in hypertriglyceridaemia results from enhanced hepatic synthesis of the enzyme.